The Effect of Motivation and Work Training on Sustainable Performance Through Employee Job Satisfaction at PT Erlian Prima Group - Fitriyani, Anisa; Subiyanto, Didik; Lysander, Mohammad Ahyar Syafwan (Universitas Muhammadiyah Pontianak, 2026)
This study examines the impact of work motivation and job training on sustainable performance, with job satisfaction as a mediating variable among PT Erlian Prima Group employees. Using a quantitative approach and saturated sampling of 52 respondents, data were analyzed via SPSS 26. Results show that work motivation and job training significantly influence sustainable performance and job satisfaction. Job satisfaction also significantly affects sustainable performance and mediates both predictors. Together, the variables explain 76.6% of job satisfaction variance. These findings highlight the critical role of motivation, training, and satisfaction in achieving sustainable employee performance.